The Characteristic of Toddlers Reproductive Health in Posyandu Matahari, Blimbing, Malang, East Java, Indonesia - Kurnia Penta Seputra; Besut Daryanto; Zen A Prasetyo; Johanes Dwi Meiyanto; Hamdan Yuwafi Naim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background & Objective: The screening of reproductive health plays an essential role of early detectionof reproductive health disorder. There was a study which suggested that there was at least one congenitaldisorder every 100 live births. The Congenital reproductive disorder are mostly found in type of hypospadias,enlarged clitoris, micropenis, fusion of labia majora, and genital ambiguity. Data collected in Saiful AnwarGeneral Hospital revealed that period of 2012-2017 there were 109 hypospadias cases, 64 undescendedtesticle cases, and 80 cases of testicular torsion. However, for the Disorders of Sex Development cases, therewere found 12 cases from period of 2015-2017, with mean age was school age (8-14 years old). Unfortunately,there was no data of congenital reproductive disorder in toddlers, thus we conducted screening of toddlersreproductive health in PosyanduMatahari which located in Malang, East Java, Indonesia in order to find outthe number of incidence of toddlers congenital reproductive disorder and held the early detection.Materials & Methods: This is observational descriptive study. Screening was held in PosyanduMatahariwhich located in GedungSerbagunaRw. 14, Bunulrejo, Jodipan, Blimbing, Malang, in October 27, 2018. Itused method of physical examination (age, weight, height, external genital examination), and if it was foundsuspicious of disease or disorder of toddler congential reproductive health, thus it would be given referral toappropriate health careResults: This screening event involved 46 toddlers (1-5 years old). From 46 toddlers, there were 14 toddlers(30.43%), 10 toddlers suffered from Phimosis (21.74%), 1 toddler with Hydrocele (2.17%), dan 3 toddlerssuffered from UDT (6.52), who were referred to urology clinic in Saiful Anwar General Hospital to undergofurther examination and treatment.Conclusion:The incidence of toddlers reproductive disorder of this event was 30,43%, showed that thisage group (1-5 years old) had significant amount of congenital reproductive disorder and screening playedimportant role for early detection and improving parental knowledge to prevent the delay of treatment forreproductive disorder.